Voluntary Disclosure Programs for Tax Evaders - Heiner Schmittdiel (Tinbergen Institute, 2015)
In this paper, we develop a model that can explain why governments may want to choose to offer a voluntary disclosure program that allows people who withheld taxes to turn themselves in without punishment. We find that such a leniency rule not only increases government revenue when it comes as a surprise, but even when taxpayers anticipate it.
Keywords: H26; K34; K40; 330; Tax compliance; voluntary disclosure; guilt